Identification of SRS transcription factor family in Solanum lycopersicum, and functional characterization of their responses to hormones and abiotic stresses - Wang Lu; Yan Wang; Yuan Shi; Qin Liang; Xiangyin Lu; Deding Su; Xin Xu; Julien Pirrello; Ying Gao; Baowen Huang; Zhengguo Li (BMC Plant Biology)
Abstract The SHI RELATED SEQUENCE (SRS) family plays a vital role in the development of multiple plant organs such as floral meristem determinacy, organ morphogenesis, and signal transduction. Nevertheless, there is little understanding of the biological significance of tomato SRS family at this point. Our research identified eight SlSRS family members and classified them into three subfamilies based on phylogenetics, conserved motifs, and characteristic domain analysis. The intraspecies and interspecies collinearity analysis revealed clues of SRS family evolution. Many cis-elements related to hormones, stresses, and plant development can be found in the promoter region of SlSRS genes. All of eight SlSRS proteins were located in the nucleus and possessed transcriptional activity, half of which were transcriptional activators, and the other half were transcriptional repressors. Except for SlSRS1, which showed high transcript accumulation in vegetative organs, most SlSRS genes expressed ubiquitously in all flower organs. In addition, all SlSRS genes could significantly respond to at least four different plant hormones. Further, expression of SlSRS genes were regulated by various abiotic stress conditions. In summary, we systematically analyzed and characterized the SlSRS family, reviewed the expression patterns and preliminarily investigated the protein function, and provided essential information for further functional research of the tomato SRS genes in the determination of reproductive floral organs and the development of plants, and possibly other plants.